Lemierre’s syndrome associated with hypervirulent Klebsiella pneumoniae: A case report and genomic characterization of the isolate - Lee, Seung Eun; Mushtaq, Ammara; Gitman, Melissa; Paniz-Mondolfi, Alberto; Chung, Marilyn; Obla, Ajay; Sordillo, Emilia M.; Nowak, Michael D.; van Bakel, Harm; Ramírez, Juan David; Muñoz, Marina; Lee, Mikyung (IDCases, 2021)
We describe a case of Lemierre’s syndrome (LS) caused by a hypervirulent strain of Klebsiella pneumoniae in a 63-year-old female with hypertension, hyperlipidemia, and diabetes mellitus, who presented with right neck pain and fevers. Computerized tomography of the neck and chest revealed an occluded right internal jugular vein secondary to thrombosis and septic emboli in lungs. Blood cultures grew K. pneumoniae. The patient was treated with ampicillin-sulbactam and then transitioned to amoxicillin-clavulanate to complete a 6-week course of antibiotics, and a 3-month course of rivaroxaban. String test of the K. pneumoniae isolate was positive at 2 cm. Whole genome sequencing identified several genes associated with the hypervirulent strain, notably the genes encoding for aerobactin (iucA and iucB) and salmochelin (iroB) iron acquisition systems. LS can rarely be caused by K. pneumoniae. Clinicians should monitor for known complications, such as septic emboli in patients with LS.